Exploration of Islamic Religious Education Involves The Independent Learning Curriculum in The Digital Era - Ahmad Hariyadi; Muhajir Musa; Moh. Solehuddin; Reviandari Widyatiningtyas (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The educational process aims to change human life in a better direction. In Islam, humans are caliphs on earth, so they are responsible for civilization here. With the continuous development of the times, the government enforces an independent learning curriculum for good achievements. The independent curriculum, coupled with current digital developments, provides students with active, creative, innovative, and critical thinking about learning, especially in Islamic education. The paradigm of modern Islamic religious education in the digital era as a form of novelty to achieve good competence in the digital world. So this research aims to explore Islamic religious education involving the independent learning curriculum in the digital era, with produce findings about the implementation of Islamic education and the preparation of religious education to continue to develop in adjusting the continuity of education in the digital era. The data obtained from this study used library data available in books, articles, online media source documents, and other reliable sources.